Budidaya Lebah Tanpa Sengat (Hymenoptera : Apidae) di Kabupaten Muara Enim, Sumatera Selatan - Yudianti, Yudianti; Herlinda, Siti; Puspita Sari, Jelly Milinia; Rindiani, Dellania Eka; Marlina, Dewi Nini; Netaria, Netaria (Seminar Nasional Lahan Suboptimal, 2023)
Yudianti, Y., Herlinda, S., Millinia, J., Rindiani, D. E., Marlina, D., & Netaria, N. (2023). Meliponiculture of Stingless bee (Hymenoptera: Apidae) in Muara Enim Regency, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang  21 Oktober 2023. (pp. 333-344). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The survival of stingless bee populations is threatened, partly due to loss of natural habitat due to land use change and deforestation. This study aimed to determine how to cultivate stingless bees in Muara Enim Regency, South Sumatra. The method used is survey or direct observation in the field to observe tools and materials for making nest boxes, multiplying colonies, harvesting honey, packaging honey, marketing and conducting interviews with stingless bee farmers. This study interviewed one stingless bee farmer. Tools and materials used in making nests include trees, boards, nails, hammers, zinc, plastic, bricks, saws. The development and number of colonies depends on the forage plants around the hive. Honey harvesting tools and materials include a honey suction machine, sticks/toothpicks and honey storage. Honey packaging uses labeled syrup bottles. The resulting stingless bee honey products are sold in the Prabumulih traditional market, Palembang, social media and come directly to the stingless bee cultivation garden. The results showed that stingless bee cultivation is carried out by starting with land preparation, then finding colonies, moving colonies, maintaining colonies and harvesting honey. Stingless bee cultivation methods should be socialized to the community so that they can practice stingless bee cultivation which is beneficial for agricultural ecosystems, human health and also as a source of livelihood.